Analysis of the Development and Thermal Properties of Chitosan Nanoparticle-Treated Palm Oil: An Experimental Investigation - Varadharaja Kirthika; Chanaka Galpaya; Ashan Induranga; Amanda Sajiwanie; Vimukthi Vithanage; Kaveenga Rasika Koswattage (Nanomaterials)
This study is an effort to optimize the thermal properties of refined, bleached, and deodorized (RBD) oil by incorporating bionanoparticles. This study investigates the impact on thermal conductivity and thermal diffusivity by incorporating chitosan nanoparticles (CS-NPs) at different temperatures with varying weight fractions of NPs. To the best of our knowledge, these synthesized CS-NPs from oyster mushrooms (Pleurotus ostreatus) and commercial marine-sourced CS-NPs are used for the first time to prepare nanofluids. These nanofluids offer high potential for industrial applications due to their biodegradability, biocompatibility, and nontoxicity. Fungal-sourced chitosan is a vegan-friendly alternative and does not contain allergic compounds, such as marine-sourced chitosan. The CS-NPs were synthesized using a chemical and mechanical treatment process at three different amplitudes, and CS-NPs at amplitude 80 were selected to prepare the nanofluid. Chitin, chitosan, and CS-NPs were characterized by the FTIR-ATR method, while the size and morphology of the CNs were analyzed by SEM. Thermal conductivity and thermal diffusivity of nanofluids and base fluid were measured using a multifunctional thermal conductivity meter (Flucon LAMBDA thermal conductivity meter) by ASTM D7896-19 within the temperature range 40–160 °C with step size 20. The thermal conductivity values were compared between commercial CS-NPs and synthesized CS-NPs treated with RBD palm olein with different weight percentages (0.01, 0.05, and 0.1 wt.%). It was confirmed that the thermal properties were enhanced in both kinds of nanoparticles added to RBD palm olein, and higher enhancement was observed in fungal-sourced CS-NPs treated with RBD palm olein. Maximum enhancement of thermal conductivity of commercial and synthesized CS-NPs treated with RBD palm olein were 4.28% and 7.33%, respectively, at 0.05 wt.%. Enhanced thermal conductivity of RBD palm olein by the addition of CS-NPs facilitates more effective heat transfer, resulting in quicker and more consistent cooking and other potential heat transfer applications.